Physiological and developmental mechanism of regressive molt in a damp-wood termite Hodotermopsis sjostedti - Kobayashi, Kenta; Oguchi, Kohei; Miura, Toru (Frontiers in Ecology and Evolution, 2023)
In some species of termites, a part of nymphs can undergo “regressive molt”, in which imaginal characters such as wing buds and body size are reduced. The function of regressive molt is thought to be a regulatory mechanism controlling caste composition in a colony. However, little is known about the physiological and developmental processes resulting in the regressive molt. In this study, therefore, regressive molt was observed in a damp-wood termite Hodotermopsis sjostedti, under rearing conditions, and histological and morphological observations during regressive molt (especially the reduction of wing buds) were carried out. It was found that, in the focal species, nymphs with wing buds were classified into three morphological types. Almost all nymphs with swollen wing buds (Type 1) differentiated into alates, while nymphs with pigmented wing buds (Type 2) or with flat wing buds (Type 3) underwent regressive molts to become pseudergates (workers). Through the regressive molt, a part of nymphs differentiated into presoldiers or neotenic reproductives. Histological observations showed that, in nymphs undergoing regressive molt, epithelial tissue of wing buds was degenerated. Consistently, real-time qPCR analyses revealed that, apoptosis-related factors were up-regulated in the thoracic parts of Type-3 nymphs. Furthermore, expression analyses on developmental and endocrine factors by real-time qPCR were carried out, showing that, the expression pattern of these factors in regressive molt is nearly identical to that in stationary molt. These results suggest that the differentiation fate of nymph is determined during the intermolt period before the differentiation into Type-1 or Type-2/3 nymphs. The regressive molt itself would be almost identical to stationary molt.